The Relevance of a Conductor Competition for the Study of Emotional Synchronization Within and Between Groups in a Natural Musical Setting - Chabin, Thibault; Tio, Grégory; Comte, Alexandre; Joucla, Coralie; Gabriel, Damien; Pazart, Lionel (Frontiers in Psychology, 2020)
Group emotional dynamics are a central concern in the study of human interaction and communication. To study group emotions, the social context of a musical event in ecological conditions may overcome several limits of laboratory experiments and could provide a suitable ecological framework. This study aimed to evaluate if cultural events such as a conductor competition could welcome scientific research for the study of group emotional sharing. We led an observational study, which suggests that in this particular context, public, musicians and jury would agree to participate and to wear neurophysiological and physiological devices to monitor their emotional state during the competition. Self-administrated scales showed that, in the context of a musical competition, members of the public felt strong musical emotions such as music chills. Our results suggest that such a specific competition design is a suitable experimental model to lead an experiment under ecological conditions to effectively investigate collective emotional synchronisation. In the future, with the implementation of an acquisition system recording synchronous neurophysiological data for a large group of participants, we may be able to highlight mechanisms involved in emotional synchronisation in a musical ecological framework.